Treatment of panurethral strictures using one side dissection dorsal onlay buccal mucosal graft urethroplasty - Gede Wirya Diptanala Putra Duarsa; Gede Wirya Kusuma Duarsa; Ida Bagus Putra Pramana; Paksi Satyagraha (Indoscholar, 2021)
The management of panurethral stricture was still challenging and controversial. We presented a case of pan urethral strictures management by using a one-sided dissection of dorsal onlay buccal mucosal graft (BMG) urethroplasty (Kulkarni technique). A 53-years old man admitted with panurethral stricture who had previously undergone several procedures. Bipolar micturition cystourethrography procedure revealed 17 cm stricture length. One-sided dissection dorsal onlay buccal mucosal graft urethroplasty was performed. No drain was placed. The Foley catheter was removed four weeks after surgery, and the results of the micturition were favourable. No fistulae were found at a straight erection and meatus at a normal position. The postoperative flow rate (Qmax) was 24.9 ml/second. As a conclusion Kulkarni technique urethroplasty gained good outcome for panurethral stricture in our case.